The Effect of Growmore and BAP (Benzyl Amino Purine) Concentrations on The Growth of Dendrobium bigiante agrihorti Orchid In-Vitro - Shofiyah Zanirah; Sutini Sutini; Didik Utomo Pribadi (The University of Lampung, 2023)
The increase in production of Dendrobium bigiante agrihorti orchids by in vitro culture is to produce numerous and uniform seedlings. This study aimed to determine the effect of Growmore and BAP concentrations on the growth of orchid plantlets. The experiment consisted of two factors namely Growmore concentration (0; 3; 6; 9 ppm), and BAP concentrations (0; 1; 3; 5 ppm). The factors combination on ½ MS media was repeated 3 times and obtained 48 experimental units. Observation parameters included the percentage of live plantlets, number of roots, number of leaves, plant height (cm), and wet weight of plantlets (g). Results showed that a Growmore concentration of 3 ppm had a significant effect on the number of roots and plant height at 4.36 units and 4.17 cm. BAP concentration of 3 ppm also had a significant effect on the number of roots, plant height, and wet weight of respectively 4.72 units, 3.22 cm, and 0.63 g. A combination of Growmore 3 ppm + BAP 0 ppm produced the largest percentage of live planets at 100% and plant height at 7.37 cm, Growmore 9 ppm + BAP 0 ppm produced the largest number of roots at 6.33 units and Growmore 6 ppm + BAP 3 ppm produced the largest number of leaves at 8.78 strands. Keywords: BAP, Dendrobium bigiante, Growmore.